You Don’t Bend It Like Beckham if You’re Female and Reminded of It: Stereotype Threat Among Female Football Players - Grabow, Hilmar; Kühl, Melanie (Frontiers in Psychology, 2019)
Originally, the stereotype threat effect – poorer performance due to a fear of fulfilling a negative stereotype about one’s group – was demonstrated for cognitive tasks (e. g. Steele & Aronson, 1995, or Steele, 1997). Drawing on the widespread stereotype of women being unable to play football we experimentally tested (N = 80) whether a respective threat affected female football players’ goal scoring precision, i. e. a complex and demanding motor task. Those participants who were reminded of the stereotype scored significantly less hits than those not reminded. Additionally, deviations from the instruction during task execution (e. g. shooting from another distance than demanded or using the wrong foot) were recorded. Stereotype threat did not affect this comparatively more cognitive task of following instructions correctly. In order to explore underlying mechanisms of the observed stereotype effect, several potential mediators, e. g. measures of cognitive interference, or collective identification, were tested. None emerged as an unquestionable link between threat and motor performance. We discuss, however, why collective identification – in comparison to cognitive demand – appears to be the more promising explanatory concept.